Sequence not salvage - Sborov, Douglas W.; Fortuna, Gliceida Galarza; Hayden, Patrick J. (British journal of haematology, 2024)
Chimeric antigen receptor T‐cell (CAR‐T) therapy for the treatment of multiple myeloma (MM) has fundamentally changed the relapsed and refractory therapeutic landscape, but the disease remains incurable. Two CAR‐T products, idecabtagene vicleucel (ide‐cel; Abecma) and ciltacabtagene autoleucel (cilta‐cel, Carvykti), have been FDA‐ and EMA‐approved for the treatment of relapsed/refractory MM (RRMM); both target B‐cell maturation antigen (BCMA), a surface glycoprotein highly expressed on MM cells. Despite deep and durable responses following CAR‐T therapy, most patients will need subsequent treatment, and the optimal next‐line therapy is presently unclear. Commentary on: Liu et al. Outcomes in patients with multiple myeloma receiving salvage treatment after BCMA‐specific CAR‐T therapy: A retrospective analysis of LEGEND‐2. Br J Haematol 2024;204:1780‐1789.